Fabrication of Human Body Phantom for Body Centric Communication Systems at 2.4 GHz - Mohd Nizam, Nurul Najwa; Kamardin, Kamilia; Yamada, Yoshihide; Idris, Izni Husna; Abd Rahman, Nurul Huda; Mad Kaidi, Hazilah (International Journal of Integrated Engineering, 2020)
This research is intending to investigate the human skin phantom’s dielectric constant. The phantom will be used to test the electromagnetic compatibility later on since it can be harmful if it is directly tested on real human body. The human body phantom is made to have similar property as a skin tissue, at the operating frequency of 2.4 GHz. A methodology of the process is discussed. The phantom is fabricated, tested and measured. A fabricated phantom with the desired permittivity of εr and conductivity of σ values; are controlled by the amount of polyethylene powder and sodium chloride. The information on dielectric constant of the phantom based on measured values of εr and σ will be determined. The factors in making a good phantom is discussed. A good level of agreement is observed between simulation and measurement results.